Exploring the metaverse in the education of healthcare students: A scoping review - Andrea Bernardes; Lucas Gardim; Agostinho A C Araújo; Rodrigo Jensen; Raquel Acciarito Motta; Denise Maria de Almeida; Roberta Rubia de Lima; Heloísa Helena Ciqueto Peres (Universidade de São Paulo, 2024)
Objective: to map the literature on the incorporation of the metaverse in the education of undergraduate healthcare students. Method: scoping review following the recommendations of the JBI and Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews (PRISMA-ScR), performed on Web of Science, Medical Literature Analysis and Retrieval System Online (MEDLINE) via PubMed, Embase, Scopus, Cumulative Index to Nursing and Allied Health (CINAHL), Latin American and Caribbean Health Sciences Literature (LILACS) and ProQuest. Results: a total of 23 records were included, published between 2020 and 2023, and developed in 10 countries. The metaverse allows the simulation of hypothetical cases, making education interactive and attractive. However, it faces limitations, including the possibility of depersonalizing students, concerns about data security and privacy, and the high cost of implementing and maintaining its infrastructure. Conclusion: the metaverse enables the development of clinical competencies that support the construction of students' professional identity. However, it may not be equitable, as it requires resources and knowledge from educators to implement it, contributing to increasing inequality in the education of healthcare students.